Effects of colloidal nano-SiO2 on the immobilization of chloride ions in cement-fly ash system. (July 2020) - Liu, Xiaohai; Ma, Baoguo; Tan, Hongbo; Zhang, Ting; Mei, Junpeng; Qi, Huahui; Chen, Pian; Wang, Jingran
Abstract: This paper investigates effect of colloidal nano-SiO2 (CNS) on chloride immobilization of cement-fly ash (FA) system composed of 70% cement and 30% FA from 7 d to 90 d age. The mechanism was revealed in terms of migration resistance, chemical binding, and physical binding; and each aspect was determined with corresponding measurements, including microstructure of hydrates examined by XRD, EDS, TGA and NMR, and pore structure evaluated by MIP. Results reveal that the CNS dosage influenced immobilized chloride ratio (ICR). 0.5% CNS promoted the ICR, while more than 0.5% CNS decreased ICR. The promotion by 0.5% CNS was derived from the refined pore structure and the increased amount of C–S–H gel, which could enhance the migration resistance and physical binding; the decrease by more than 0.5% CNS was because of the reduced amount of chloroaluminates and the decreased Ca/Si ratio, leading to the decline in chemical binding and physical binding. Furthermore, curing age also affected ICR. 28-day ICR was higher than that at 7 d or 90 d. The increase of ICR from 7 d to 28 d was attributed to the refinement of pore structure and the increase in amount of chloroaluminates and C–S–H gel; reduction from 28 d to 90 d age was due to the negative effects including the decrease in content of chloroaluminates and the reduced Ca/Si ratio. The findings are expected to give new insight into the effect of nano-SiO2 on performance of cement-based materials.